Sealing member and power storage body
Patent Information
- Application Number
- CN202180066216.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-09-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-09-30
AI Technical Summary
[0021] According to the present invention, the object is to provide a sealing component that can be easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, and can maintain excellent sealing performance at high temperatures for a long time, while suppressing moisture permeation to a higher level than the prior art, and suppressing moisture intrusion to a high level even at high temperatures.
Smart Images

Figure CN116323709B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to sealing components and energy storage elements. Background Technology
[0002] Non-aqueous electrolyte secondary batteries and other energy storage devices are used in a wide range of electronic and electrical equipment.
[0003] Patent document 1 discloses a flat non-aqueous electrolyte secondary battery, which is a flat non-aqueous electrolyte secondary battery in which a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte are housed in a battery container consisting of a battery shell, a sealing plate and a gasket. The gasket is characterized in that the material of the gasket is composed of a tetrafluoroethylene perfluoroalkyl vinyl ether copolymer (PFA resin) with a fluorine content of 70 mol% to 85 mol% and a melt flow rate (MFR) of 20 g / 10 min to 45 g / 10 min.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-056079 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] The purpose of this invention is to provide a sealing component that can be easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, maintains excellent sealing performance at high temperatures for a long period of time, and can suppress moisture permeation to a higher level than the prior art, and can suppress moisture intrusion to a high level even at high temperatures.
[0009] Methods for solving problems
[0010] According to the present invention, a sealing component is provided, which contains a copolymer containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of perfluoro(propyl vinyl ether) units is 4.0% to 6.0% by mass relative to all monomer units, and the melt flow rate of the copolymer is 26 g / 10 min to 37 g / 10 min.
[0011] The thickness of the sealing component of the present invention is preferably 0.5 mm to 2.5 mm.
[0012] The sealing area of the sealing component of the present invention is preferably 0.5 cm². 2 ~50cm 2 .
[0013] In the sealing component of the present invention, the melting point of the above copolymer is preferably 301°C to 317°C.
[0014] In the sealing component of the present invention, the heat of fusion of the above copolymer is preferably 24.0 mJ / mg or more.
[0015] In the sealing component of the present invention, the fluorine content of the copolymer is preferably less than 70 mol%.
[0016] In the sealing component of the present invention, every 10 of the above copolymer 6 The number of functional groups per main chain carbon atom is preferably more than 50.
[0017] The sealing component of the present invention is preferably an injection-molded body or a transfer-molded body.
[0018] In addition, according to the present invention, a storage battery is provided which includes the sealing member described above.
[0019] The energy storage device of the present invention preferably comprises: an outer can, an electrical component housed within the outer can, a cover that blocks the opening of the outer can, and an external terminal provided on the cover, wherein the sealing component is held between the cover and the external terminal.
[0020] The effects of the invention
[0021] According to the present invention, the object is to provide a sealing component that can be easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, and can maintain excellent sealing performance at high temperatures for a long time, while suppressing moisture permeation to a higher level than the prior art, and suppressing moisture intrusion to a high level even at high temperatures. Attached Figure Description
[0022] Figure 1 This is a 3D view of the battery's exterior.
[0023] Figure 2 This is a schematic cross-sectional view showing the configuration of the terminal portion of the energy storage device.
[0024] Figure 3 This is a front view of the sealing component.
[0025] Figure 4 yes Figure 3 A-A' line cross-section diagram.
[0026] Figure 5 This is a schematic cross-sectional view of the test fixture used in the water vapor leakage test. Detailed Implementation
[0027] The following describes specific embodiments of the present invention in detail, but the present invention is not limited to the following embodiments.
[0028] The sealing component of the present invention contains a copolymer containing tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units.
[0029] Patent Document 1 describes that the ability to mass-produce flat, non-aqueous electrolyte secondary batteries with high reliability and high energy density under harsh conditions such as high temperature or high humidity at low cost is a crucial issue for improving such batteries. To address this issue, Patent Document 1 uses a tetrafluoroethylene perfluoroalkyl vinyl ether copolymer (PFA resin) with a fluorine content of 70 mol% to 85 mol% and a melt flow rate (MFR) of 20 g / 10 min to 45 g / 10 min as the gasket material.
[0030] However, in recent years, the lifespan of energy storage devices has increased, so even the slow permeation of moisture through the gaskets and into the energy storage device can lead to a deterioration in energy storage performance. Therefore, there is a need for a technology that can suppress moisture permeation at a level higher than that described in Patent Document 1. Furthermore, as energy storage devices are increasingly used in high-temperature environments, it is necessary to suppress moisture infiltration into the energy storage device even at high temperatures. Patent Document 1 confirmed the discharge capacity and the presence or absence of leakage at 70°C, but a technology that prevents moisture infiltration at even higher temperatures is needed.
[0031] Discovery: By sealing the battery with a copolymer containing a copolymer with appropriately adjusted PPVE unit content and melt flow rate (MFR) of TFE and PPVE units, moisture permeation can be suppressed to a higher level than in the prior art, even at high temperatures (e.g., 95°C). Furthermore, it was also found that the sealing component containing this copolymer exhibits excellent sealing performance over a long period at high temperatures (e.g., 65°C). Therefore, by using such a sealing component to seal the battery, the sealing performance will not be compromised even when the battery experiences abnormal heat dissipation and becomes extremely hot. Moreover, such a sealing component can be easily manufactured using injection molding, and the surface of the sealing component obtained by injection molding is very smooth.
[0032] The sealing component of the present invention is based on these technical concepts. It can be easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, and can maintain excellent sealing performance at high temperatures for a long time. At the same time, it can suppress moisture permeation to a higher level than the prior art, and can suppress moisture intrusion to a high level even at high temperatures.
[0033] The sealing component of the present invention contains a copolymer that is melt-processable fluoropolymer. Melt-processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.
[0034] The content of PPVE units in the copolymer is 4.0% to 6.0% by mass relative to all monomer units. The content of PPVE units in the copolymer is preferably 5.8% by mass or less, more preferably 5.7% by mass or less, further preferably 5.6% by mass, particularly preferably 5.5% by mass or less, preferably 4.1% by mass or more, more preferably 4.2% by mass or more, further preferably 4.3% by mass or more, particularly preferably 4.4% by mass or more, and most preferably 4.5% by mass or more. By keeping the content of PPVE units in the copolymer within the above range, a sealing component that exhibits excellent sealing performance even at high temperatures, maintains excellent sealing performance at high temperatures for a long period, suppresses moisture permeation to a level higher than that of the prior art, and suppresses moisture intrusion to a high level even at high temperatures can be obtained.
[0035] The content of tetrafluoroethylene (TFE) units in the copolymer is preferably 94.0% to 96.0% by mass relative to all monomer units. More preferably, the content of TFE units in the copolymer is 94.2% by mass or more, further preferably 94.3% by mass or more, even more preferably 94.4% by mass or more, particularly preferably 94.5% by mass or more, more preferably 95.9% by mass or less, further preferably 95.8% by mass or less, even more preferably 95.7% by mass or less, particularly preferably 95.6% by mass or less, and most preferably 95.5% by mass or less. By keeping the content of TFE units in the copolymer within the above range, a sealing component that exhibits excellent sealing performance even at high temperatures, maintains excellent sealing performance at high temperatures for a long period, suppresses moisture permeation to a level higher than that of the prior art, and suppresses moisture intrusion to a high level even at high temperatures can be obtained.
[0036] In this invention, the content of each monomer unit in the copolymer is determined by... 19 The determination was performed using F-NMR.
[0037] The copolymer may also contain monomer units from monomers capable of copolymerizing with TFE and PPVE. In this case, the content of monomer units capable of copolymerizing with TFE and PPVE is preferably 0 to 2.0% by mass, more preferably 0.05% to 1.5% by mass, and even more preferably 0.1% to 0.5% by mass, relative to all monomer units of the copolymer.
[0038] Monomers capable of copolymerizing with TFE and PPVE include hexafluoropropylene (HFP) and CZ. 1 Z 2 =CZ 3 (CF2) n Z 4 (where Z)1 Z 2 and Z 3 Same or different, represented by H or F, Z 4 The denoting letter represents H, F, or Cl, and n represents an integer from 2 to 10. The vinyl monomers shown are CF2=CF-OCH2-Rf. 1 (where Rf) 1 This refers to perfluoroalkyl groups having 1 to 5 carbon atoms. Alkyl perfluorovinyl ether derivatives, etc., are also included. HFP is preferred.
[0039] The copolymer is preferably selected from at least one of the groups consisting of copolymers composed only of TFE units and PPVE units, and TFE / HFP / PPVE copolymers, and more preferably copolymers composed only of TFE units and PPVE units.
[0040] The fluorine content of the copolymer is preferably less than 70 mol%, more preferably less than 69 mol%, further preferably less than 68 mol%, particularly preferably less than 67 mol%, more preferably more than 65 mol%, and more preferably more than 66 mol%. By keeping the fluorine content of the copolymer within the above range, it is possible to obtain a sealing component that can be more easily manufactured by injection molding, exhibits superior sealing performance at high temperatures, maintains superior sealing performance at high temperatures for a longer period of time, and simultaneously suppresses moisture permeation to a higher level than existing technologies, and also suppresses moisture intrusion to a higher level at high temperatures.
[0041] The fluorine content of a copolymer can be calculated from the composition of the copolymer's monomer units.
[0042] The melt flow rate (MFR) of the copolymer is 26 g / 10 min to 37 g / 10 min. The MFR of the copolymer is preferably 28 g / 10 min or more, preferably 36 g / 10 min or less, more preferably 35 g / min or less, and even more preferably 34 g / 10 min or less. By keeping the MFR of the copolymer within the above range, a sealing component can be obtained that can be easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, maintains excellent sealing performance at high temperatures for a long period, suppresses moisture permeation to a level higher than that of the prior art, and maintains a high level of moisture ingress even at high temperatures.
[0043] In this invention, the melt flow rate of the copolymer is determined according to ASTM D1238 using a melt flow index tester, as the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm every 10 minutes at 372°C and a load of 5 kg.
[0044] MFR can be adjusted by changing the type and amount of polymerization initiator used when polymerizing monomers, and the type and amount of chain transfer agent.
[0045] per 10 of the copolymer 6 The number of functional groups per main chain carbon atom is typically more than 50, preferably 75 or more, more preferably 100 or more, and even more preferably 150 or more, with no particular upper limit, and can be up to 800. By adjusting the content of PPVE units and melt flow rate (MFR) of the copolymer, and introducing a sufficient number of functional groups into the copolymer, the carbon dioxide permeability of the sealing component obtained from the copolymer can be further improved. Furthermore, copolymers with the above-mentioned number of functional groups are easy to manufacture and can be manufactured at low cost. Therefore, by using a sealing component containing a copolymer with a sufficient number of functional groups in a battery, a battery with reduced cost and low carbon dioxide retention can be obtained. Even with a high number of functional groups in the copolymer, by appropriately adjusting the content of PPVE units and MFR, a sealing component capable of suppressing moisture permeation at a level higher than that of the prior art can be obtained. Therefore, by using a sealing component containing a copolymer with a sufficient number of functional groups, carbon dioxide generated during battery use can permeate to the outside of the battery, suppressing battery expansion while ensuring a sufficient seal.
[0046] The identification of the types of functional groups and the determination of the number of functional groups can be performed using infrared spectrophotometry.
[0047] Regarding the number of functional groups, specifically, it was determined using the following method. First, the copolymer was cold-pressed to form a film with a thickness of 0.25 mm to 0.3 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups per 1 × 10⁻⁶ functional groups in the copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0048] N = I × K / t(A)
[0049] I: Absorbance
[0050] K: Correction coefficient
[0051] t: Membrane thickness (mm)
[0052] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Additionally, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.
[0053] Table 1
[0054] Table 1
[0055]
[0056] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. -1 ).
[0057] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF, which is 1883 cm⁻¹. -1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also analyzed. -1 The total number of functional groups obtained from the absorption peak at the given location.
[0058] Functional groups are those present at the ends of the main chain or side chains of the copolymer, and those present in the main chain or side chains. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.
[0059] The aforementioned functional groups are introduced into the copolymer, for example, through chain transfer agents or polymerization initiators used in the manufacturing of the copolymer. For instance, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the copolymer's main chain. Alternatively, the aforementioned functional groups are introduced to the ends of the copolymer's side chains by polymerizing monomers containing functional groups.
[0060] By fluorinating the copolymer containing such functional groups, the number of functional groups is reduced. That is, the copolymer is preferably an unfluorinated copolymer. Furthermore, the copolymer is preferably an untreated copolymer that has not undergone stabilization treatments such as ammonia treatment.
[0061] The melting point of the copolymer is preferably 301°C to 317°C, and more preferably below 306°C. By keeping the melting point within the above range, it is possible to obtain a sealing component that can be more easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, suppresses moisture permeation to a level higher than that of the prior art, and suppresses moisture intrusion to a high level even at high temperatures.
[0062] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).
[0063] The heat of fusion of the copolymer of the present invention, as determined by differential scanning calorimetry, is preferably 24.0 mJ / mg or more, more preferably 25.0 mJ / mg or more, further preferably 28.0 mJ / mg or more, preferably 40.0 mJ / mg or less, and more preferably 38.0 mJ / mg or less. By keeping the heat of fusion within the above range, a sealing component that can be more easily manufactured by injection molding, exhibits excellent sealing performance at high temperatures, suppresses moisture permeation to a level higher than that of the prior art, and maintains a high level of moisture intrusion suppression even at high temperatures can be obtained.
[0064] The water vapor permeability of the copolymer is preferably 11.5 g·cm / m. 2 The following, and more preferably, is 10.5 g·cm / m 2 The following describes how, by ensuring the water vapor permeability of the copolymer is within the aforementioned range, a sealing component capable of suppressing moisture permeation to a level higher than that of the prior art can be obtained. Using such a sealing component, an energy storage device that effectively suppresses the permeation of external moisture can be obtained. The water vapor permeability of the copolymer can be reduced by adjusting the PPVE unit content and MFR of the copolymer.
[0065] The water vapor permeability of a copolymer can be determined by measuring the mass of water vapor permeating through the copolymer membrane at 95°C for 30 days. A smaller value indicates less water vapor permeation / diffusion within the sealed component, and better suppression of water vapor permeating from the external to the internal surfaces of the sealed component. Therefore, by using a sealed component containing a copolymer with low water vapor permeability, a battery with high levels of moisture permeability can be obtained.
[0066] The water vapor leakage of the copolymer is preferably 0.0035 g / 1000 hours or less, more preferably 0.0033 g / 1000 hours or less, and the lower limit is not particularly limited, and can be 0.0015 g / 1000 hours or more. By keeping the water vapor leakage of the copolymer within the above range, a sealing component that can suppress moisture intrusion at high temperatures can be obtained, and by using such a sealing component, an energy storage device that further suppresses moisture intrusion can be obtained. The water vapor leakage of the copolymer can be reduced by adjusting the content of PPVE units and MFR of the copolymer.
[0067] The water vapor leakage of the copolymer can be measured by using a gasket (outer diameter Φ17.7mm, inner diameter Φ14.3mm, thickness 1.6mm) obtained by copolymer injection molding, under conditions of 95°C and 1000 hours, measuring the reduction in mass of water inside the space sealed by the gasket. Regarding the water vapor leakage of the copolymer, when the copolymer is made into a gasket, it is the sum of the amount of water vapor that permeates through the gasket in the surface direction and the amount of water vapor that permeates through the contact surface between the gasket and the component of the energy storage device. The smaller this value, the better the surface-direction moisture infiltration is suppressed when the copolymer is made into a gasket. Therefore, by using a gasket containing a copolymer with low water vapor leakage at 95°C, a sealing component that can suppress moisture infiltration at high temperatures can be obtained, and an energy storage device that can suppress moisture infiltration to a high level even at high temperatures can be obtained.
[0068] The storage modulus (E') of the copolymer at 150°C is preferably 10 MPa or more, more preferably 50 MPa or more, more preferably 1000 MPa or less, more preferably 500 MPa or less, and even more preferably 200 MPa or less. By ensuring that the storage modulus (E') of the copolymer at 150°C is within the above range, a sealing component exhibiting excellent sealing performance at high temperatures can be obtained. By using such a sealing component, a battery whose sealing performance is not further compromised even under abnormally high temperatures can be obtained.
[0069] Storage modulus (E') can be determined by dynamic viscoelasticity measurement in the range of 30℃ to 250℃ under conditions of heating rate of 2℃ / min and frequency of 10Hz.
[0070] The surface pressure of the copolymer at 150°C is preferably 0.20 MPa or more, more preferably 0.25 MPa or more, but the upper limit is not particularly limited and can be 2.5 MPa or less. Sealing components containing copolymers with high surface pressure at 150°C exhibit excellent sealing performance at high temperatures. Therefore, by using sealing components containing such copolymers, it is possible to obtain energy storage devices whose sealing performance is not further compromised even under abnormally high temperatures. The surface pressure of the copolymer at 150°C can be increased by adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer.
[0071] The surface pressure can be calculated as follows: Under the condition that the test piece is deformed at a compression rate of 50%, it is placed at 150°C for 18 hours, the compression is released, and after being placed at room temperature for 30 minutes, the height of the test piece (the height of the test piece after compression deformation) is measured. The height of the test piece after compression deformation and the storage modulus (MPa) at 150°C are calculated by the following formula.
[0072] Surface pressure at 150℃ (MPa) = (t2 - t1) / t1 × E'
[0073] t1: Original height (mm) of the test piece before compression deformation × 50%
[0074] t2: Height of the test piece after compression deformation (mm)
[0075] E': Energy storage modulus at 150℃ (MPa)
[0076] The preferred carbon dioxide permeability of the copolymer is 1515 cm⁻¹. 3 ·mm / (m 2 ·24h·atm) or more, preferably 1565cm 3 ·mm / (m 2 • 24h atm and above. It was found that by adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer, and simultaneously introducing a relatively large number of functional groups into the copolymer, a copolymer with a relatively high carbon dioxide permeability coefficient can be obtained. Therefore, sealing components containing this copolymer easily allow carbon dioxide to pass through, and by using such sealing components, it is possible to obtain a battery that makes it difficult for carbon dioxide to remain inside.
[0077] In this invention, the carbon dioxide transmission coefficient can be measured under test conditions of 70°C and 0% RH. The specific measurement of the carbon dioxide transmission coefficient can be performed using the methods described in the examples.
[0078] The copolymer used to form the sealing component of the present invention can be manufactured by polymerization methods such as suspension polymerization, solution polymerization, emulsion polymerization, and bulk polymerization. Emulsion polymerization or suspension polymerization is preferred as the polymerization method. In these polymerizations, conditions such as temperature and pressure, polymerization initiators, and other additives can be appropriately set according to the composition and amount of the copolymer.
[0079] Oil-soluble or water-soluble free radical polymerization initiators can be used as polymerization initiators.
[0080] Oil-soluble free radical polymerization initiators can be well-known oil-soluble peroxides, and the following substances can be cited as representative examples:
[0081] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, disec-butyl percarbonate, and di-2-ethoxyethyl percarbonate;
[0082] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;
[0083] Dialkyl peroxides such as di-tert-butyl peroxide;
[0084] Di[fluoro(or fluorochloro)acyl] peroxides; etc.
[0085] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).
[0086] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)fluoroheptanoyl)peroxide, di(ω-hydro-hexadecanoyl)fluorononanoyl)peroxide, di(perfluoropropionyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, and di... (ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoheptafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoheptafluorobutyryl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, etc.
[0087] Water-soluble free radical polymerization initiators can be well-known water-soluble peroxides, such as ammonium, potassium, and sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate; organic peroxides such as disuccinate peroxide and diglutaric acid peroxide; tert-butyl maleate peroxide; and tert-butyl hydroperoxide. Reducing agents such as sulfites can also be used in combination with peroxides, with the amount used relative to the peroxide ranging from 0.1 to 20 times.
[0088] In polymerization, surfactants, chain transfer agents, and solvents can be used, each of which can be existing and well-known substances.
[0089] As the surfactant, known surfactants can be used, such as nonionic surfactants, anionic surfactants, and cationic surfactants. Among these, fluorinated anionic surfactants are preferred, and more preferably, fluorinated anionic surfactants with straight or branched chains having 4 to 20 carbon atoms, with or without ether-bonded oxygen (i.e., oxygen atoms can be inserted between carbon atoms). The amount of surfactant added (relative to the polymerization water) is preferably 50 ppm to 5000 ppm.
[0090] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; thiols such as methyl mercaptan; and halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane. The amount of chain transfer agent added can be varied depending on the chain transfer constant of the compound used, but it is usually used in the range of 0.01% to 20% by mass relative to the polymerization solvent.
[0091] Examples of solvents include water and mixed solvents of water and alcohol.
[0092] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; hydrofluorocarbons such as CF3CFHCFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, and CF3CF2CF2CF2CF2CF2CF2H; and CH3OC2F5, CH Hydrofluoroethers such as 3OC3F5CF3CF2CH2OCHF2, CF3CHFCF2OCH3, CHF2CF2OCH2F, (CF3)2CHCF2OCH3, CF3CF2CH2OCH2CHF2, and CF3CHFCF2OCH2CF3; and perfluoroalkanes such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkanes being preferred. From the perspectives of suspension and economy, the amount of fluorinated solvent relative to the aqueous medium is preferably 10% to 100% by mass.
[0093] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. The polymerization pressure can be appropriately determined according to the type, amount, vapor pressure, polymerization temperature, and other polymerization conditions used, and is usually 0 to 9.8 MPaG.
[0094] When an aqueous dispersion containing a copolymer is obtained through polymerization, the copolymer can be recovered by precipitating it, washing, and drying. Alternatively, when a copolymer is obtained as a slurry through polymerization, the copolymer can be recovered by removing the slurry from the reaction vessel, washing, and drying. The copolymer can also be recovered as a powder by drying.
[0095] The copolymer obtained through polymerization can also be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as using a single-screw extruder, twin-screw extruder, or tandem extruder to melt-extrude the copolymer and cut it to a specified length to form granules can be employed. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the copolymer and the manufacturing method; preferably, it is between the copolymer's melting point +20°C and the copolymer's melting point +140°C. There are no particular limitations on the copolymer cutting method; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0096] The copolymer obtained by polymerization can also be fluorinated. Fluorination is carried out by contacting the unfluorinated copolymer with a fluorinated compound. Fluorination converts thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2, as well as relatively thermally stable functional groups such as -CF2H, into the extremely thermally stable -CF3. As a result, the total number (number of functional groups) of the copolymer (-COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and -CF2H) can be reduced.
[0097] There are no particular limitations on fluorine-containing compounds; examples of fluorine radical sources that generate fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).
[0098] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0099] The conditions for fluorination are not particularly limited; the molten copolymer can be brought into contact with a fluorinated compound. However, it is generally carried out at a temperature below the melting point of the copolymer, preferably between 20°C and 240°C, and more preferably between 100°C and 220°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. Fluorination is preferably carried out by bringing the unfluorinated copolymer into contact with fluorine gas (F2 gas).
[0100] Sealing components may contain other components as needed. Examples of such components include fillers, plasticizers, pigments, colorants, antioxidants, UV absorbers, flame retardants, anti-aging agents, antistatic agents, and antibacterial agents.
[0101] Among the other components mentioned above, a filler is preferred. Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber.
[0102] As described above, the sealing component may contain other components besides the copolymer. From the perspective of fully utilizing the excellent properties of the copolymer, it is preferable that the content of other components is low, and most preferably that no other components are contained. Specifically, the content of other components relative to the mass of the sealing component is preferably 30% by mass or less, more preferably 10% by mass or less, and most preferably 0% by mass, that is, the sealing component does not contain any other components. The sealing component may be composed solely of the copolymer.
[0103] Sealing components can be manufactured by molding copolymers or compositions containing copolymers and other components into desired shapes or sizes. Examples of methods for manufacturing such compositions include: dry mixing of the copolymer with other components; pre-mixing the copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; and so on.
[0104] The method for molding the above-mentioned copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, and transfer molding. Among these methods, compression molding, injection molding, or transfer molding are preferred because they enable high-productivity production of sealing components; therefore, injection molding or transfer molding is more preferred. In other words, because they enable high-productivity production, the sealing component is preferably an injection-molded body or a transfer-molded body.
[0105] The sealing component of the present invention can be used, for example, as a gasket or sealing pad. Additionally, the sealing component of the present invention can also be suitable as an insulating component such as an insulating gasket or insulating sealing pad. A sealing component is a component used to prevent leakage of liquid or gas or the intrusion of liquid or gas from the outside. An insulating component is a component used for electrical insulation.
[0106] The sealing component of the present invention is suitable for use as a sealing component for sealing a battery. Next, a battery according to one embodiment of the present invention will be described with reference to the accompanying drawings.
[0107] Figure 1The shown battery is a sealed, square secondary battery. The battery 10 includes an outer can 1 and a cover 2. The outer can 1 has an opening (not shown) at its upper part opposite to the bottom surface 3. The outer can 1 is made of, for example, aluminum, aluminum alloy, or stainless steel. The battery 10 has a voltage of, for example, 3.0V or higher.
[0108] The outer can 1 contains electrical components such as generators (not shown), and the opening of the outer can is sealed by a cover 2. The periphery of the cover 2 is joined to the edge of the opening of the outer can 1.
[0109] The cover 2 is provided with an injection hole for injecting electrolyte into the outer container 1. As the electrolyte, one or more known solvents such as propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate can be used. An electrolyte containing dissolved electrolyte can be used. As the electrolyte, there are no particular limitations; LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, and cesium carbonate can be used.
[0110] After the electrolyte is injected into the outer tank 1 through the injection hole, a plug 5 is installed in the injection hole, and the plug 5 is joined to the edge of the injection hole of the cover 2. The joining can be performed by laser welding.
[0111] The cover 2 is provided with a first external terminal 4A and a second external terminal 4B. Externally generated power is supplied to electrical components and stored via the first external terminal 4A and the second external terminal 4B. Additionally, power is supplied to external loads. For example, the first external terminal 4A is the positive terminal, and the second external terminal 4B is the negative terminal. The first external terminal 4A is, for example, made of aluminum or an aluminum alloy. The second external terminal 4B is, for example, made of copper or a copper alloy.
[0112] To ensure that the first external terminal 4A and the second external terminal 4B are electrically insulated from the cover 2, a sealing component 6 and an insulating component 7 are provided on the cover 2. Figure 2 This is a schematic cross-sectional view showing the configuration of the terminal portion of the energy storage body. The materials used to construct the first external terminal and the second external terminal are usually different from those used in the location of the cover 2, but other configurations can be the same. Therefore, in the following description, an example of the first external terminal 4A will be given.
[0113] like Figure 2 As shown, the first external terminal 4A has: a terminal head 41A with a cuboid block shape and a cylindrical shaft portion 42A. The terminal head 41A has a lower surface 43A with a rectangular shape, and the shaft portion 42A protrudes from the lower surface 43A of the terminal head 41A.
[0114] like Figure 2 As shown, the sealing member 6 has: a cylindrical portion 61, a flange portion 62 that extends radially from an opening on one side of the cylindrical portion 61, and a sidewall portion 63 that rises from the periphery of the flange portion 62.
[0115] The cylindrical portion 61 is externally fitted into the shaft portion 42A of the first external terminal 4A, and the abutting surface 61A of the inner circumference of the cylindrical portion 61 abuts against the outer circumference surface of the shaft portion 42A. In addition, the cylindrical portion 61 is inserted into the through hole of the cover 2, and the abutting surface 61B of the outer circumference of the cylindrical portion 61 abuts against the inner circumference surface of the through hole of the cover 2.
[0116] The flange 62 is clamped by the cover 2 and the first external terminal 4A, and the abutting surface 62A of the flange 62 abuts against the lower surface 43A of the first external terminal 4A. Additionally, the abutting surface 62B of the flange 62 abuts against the surface of the cover 2. The flange 62 could also be clamped by the cover 2 and the external terminal 4A using an adhesive layer, but in the battery 10, the flange 62 directly abuts against the cover 2 and the external terminal 4A, ensuring the airtightness of the battery. In the battery 10, the lower surface 43A of the first external terminal 4A and the surface of the cover 2 are flat, but protrusions, height differences, etc., can also be provided on either or both of the lower surface 43A of the first external terminal 4A and the surface of the cover 2. By clamping the flange 62 with the cover 2 and the external terminal 4A, the compression ratio of a portion of the flange 62 is greater than that of other portions, thereby ensuring the airtightness of the battery. Alternatively, in the energy storage body 10, each contact surface of the flange portion 62 is flat, but a protrusion or inclination may be provided on one or both of the contact surfaces of the flange portion 62. The flange portion 62 is clamped by the cover 2 and the external terminal 4A, so that the compression ratio of a part of the flange portion 62 is greater than that of the other parts, thereby ensuring the airtightness of the energy storage body.
[0117] When the cylindrical portion 61 and flange portion 62 of the sealing component 6 are compressed, the sealing component 6 abuts against the first external terminal 4A and the cover 2, thereby ensuring the airtightness of the battery.
[0118] In addition to appropriately adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer forming the sealing component 6, the thickness of the sealing component 6 is also appropriately adjusted, thereby further improving the airtightness of the battery. The thickness of the sealing component is preferably 0.5 mm to 2.5 mm, more preferably 2.0 mm or less, further preferably 1.5 mm or less, particularly preferably 1.2 mm or less, and most preferably 1.0 mm or less. A smaller sealing component thickness tends to reduce the water content permeating through the sealing component; however, if the sealing component thickness is too small, sufficient resilience cannot be obtained, and the water content leaking out from the contact surface between the sealing component and the battery component may not be sufficiently reduced. By appropriately adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer and appropriately adjusting the thickness of the sealing component, the water content permeating through the sealing component can be reduced, and the water content leaking out from the contact surface between the sealing component and the battery component can also be reduced.
[0119] Figure 3 This is a front view of sealing component 6. Figure 4 This is a cross-sectional view of the sealing component 6 along line A-A'. In this invention, the thickness of the sealing component refers to the thickness of the portion that contributes to the sealing of the energy storage element. Figure 4 The sealing component 6 shown has thicknesses d and e. For example... Figure 4 As shown in the sealing component, the thicknesses d and e can be different or the same. Regardless of whether the thicknesses d and e are the same or different, it is preferable that their thicknesses have been appropriately adjusted. Furthermore, considering the production efficiency of the sealing component, since it is preferable that the variation in thickness is small, the overall thickness of the sealing component can be adjusted to the above-mentioned range. Figure 4 In the sealing component shown, not only the thicknesses d and e, but also the thickness f are appropriately adjusted to the above range.
[0120] In addition to appropriately adjusting the content of PPVE units and the melt flow rate (MFR) of the copolymer forming the sealing component 6, appropriately adjusting the sealing area of the sealing component 6 can further improve the airtightness of the battery. The sealing area of the sealing component is preferably 0.5 cm². 2 ~50cm 2 The preferred upper limit is 35cm. 2 The upper limit for further optimization is 20cm. 2 The upper limit for the preferred size is 10cm. 2 The optimal upper limit is 5cm. 2 A more preferred lower limit is 1 cm. 2 The further preferred lower limit is 2cm. 2A smaller sealing area of the sealing component results in a greater distance between the inside and outside of the battery, further suppressing moisture intrusion. However, due to the requirement for miniaturization of the battery, existing sealing components struggle to adequately suppress moisture intrusion while reducing the sealing area. The sealing component used in this invention, by appropriately adjusting the PPVE unit content and melt flow rate (MFR) of the copolymer, enables miniaturization of the battery while simultaneously further suppressing moisture intrusion by reducing the sealing area of the sealing component.
[0121] In this invention, the sealing area of the sealing component refers to the area of the portion that helps to seal the energy storage element. Figure 2 The sealing component 6 shown represents the total area of the contact surfaces 61A, 61B, 62A, and 62B.
[0122] In addition to appropriately adjusting the content of PPVE units and the melt flow rate (MFR) of the copolymer forming the sealing component 6, the compression set of the sealing component can be appropriately adjusted, thereby further improving the sealing performance of the battery. The compression set of the sealing component is preferably 20% to 60%. The compression set of the sealing component can be calculated using the following formula.
[0123] Compression deformation rate (%) = [(thickness of the sealing component before compression) - (thickness of the sealing component in the compressed state)] / (thickness of the sealing component before compression) × 100
[0124] The maximum resilience (contact pressure) of the sealing component when deformed at a compression rate of 20% to 60% is preferably 10 MPa or higher. Figure 1 In the battery 10 shown, for example, the flange portion 62 of the sealing member 6 is deformed by the cover 2 and the first external terminal 4A with a compression deformation rate of 20% to 60%. In the compressed state, the abutment surface 62A and abutment surface 62B of the flange portion 62 exhibit a maximum pressure of more than 10 MPa against the lower surface 43A of the external terminal 4A and the surface of the cover 2, respectively.
[0125] In one implementation, Figure 3 and Figure 4 The sealing component shown has the following dimensions.
[0126] a: 4.0mm
[0127] b: 9.4mm
[0128] c: 10.6mm
[0129] d: 0.5mm
[0130] e: 0.6mm
[0131] f: 0.6mm
[0132] g: 2.8mm
[0133] h: 2.2mm
[0134] Figure 1 and Figure 2 The present invention describes a sealed, square secondary battery as an energy storage device, but other energy storage devices can also be used. The energy storage device can be a primary battery, a secondary battery, or an energy storage element. The energy storage device can also be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries that incorporate an electrolyte and a power generation element. Examples of non-aqueous electrolyte batteries include, for example, lithium-ion primary batteries, lithium-ion secondary batteries, nickel-metal hydride batteries, lithium-ion capacitors, and double-layer capacitors. They can be used as vehicle batteries or as stationary batteries.
[0135] The embodiments have been described above, but it should be understood that various changes can be made to the manner and details without departing from the spirit and scope of the claims.
[0136] Example
[0137] The present invention will then be illustrated with experimental examples, but the present invention is not limited to the experimental examples described herein.
[0138] The values for the experimental and comparative examples were determined using the following methods.
[0139] (Monomer content)
[0140] The content of each monomer unit was determined by an NMR analyzer (e.g., an AVANCE300 high-temperature probe manufactured by Bruker BioSpin).
[0141] (Mel flow rate (MFR))
[0142] According to ASTM D1238, the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm per 10 minutes was determined using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg.
[0143] (Number of functional groups)
[0144] The copolymer granules were cold-pressed to form films with a thickness of 0.25 mm to 0.3 mm. The films were then analyzed by scanning them 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer) to obtain infrared absorption spectra. A differential spectrum was then obtained, comparing it to the background spectrum of a fully fluorinated film without functional groups. The absorption peaks of specific functional groups observed in the differential spectrum were used to calculate the concentration of each 1 × 10⁻⁶ functional group in the sample. 6 The number of functional groups N per carbon atom.
[0145] N = I × K / t(A)
[0146] I: Absorbance
[0147] K: Correction coefficient
[0148] t: Membrane thickness (mm)
[0149] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in this invention are shown in Table 2. The molar absorptivity was determined from FT-IR measurements of low-molecular-weight model compounds.
[0150] Table 2
[0151] Table 2
[0152]
[0153] (Melting point (second time), heat of fusion (second time))
[0154] A differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) was used to perform a first heating from 200°C to 350°C at a heating rate of 10°C / min. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. A second heating was then performed from 200°C to 350°C at a heating rate of 10°C / min. The melting point was determined from the peak value of the melting curve generated during the second heating process, and the heat of fusion was determined from the area of the melting curve peak.
[0155] Experimental Example 1
[0156] 49.0 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 40.7 kg of perfluorocyclobutane, 1.38 kg of perfluoropropyl vinyl ether (PPVE), and 4.00 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.64 MPa, followed by 0.041 kg of a 50% methanol solution of di-n-propyl peroxide dicarbonate, to initiate polymerization. Since the pressure in the system decreased as polymerization progressed, TFE was continuously supplied to maintain a constant pressure. For every 1 kg of TFE supplied, 0.047 kg of PPVE was added, and polymerization continued for 18 hours. After releasing the TFE and restoring atmospheric pressure to the autoclave, the resulting reaction product was washed with water and dried to obtain 30 kg of powder.
[0157] TFE / PPVE copolymer granules were obtained by melt extrusion at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.). Various physical properties of the obtained granules were then determined using the methods described above.
[0158] Experiment Example 2
[0159] The pure water was changed to 34.0 L, the perfluorocyclobutane to 30.4 kg, the PPVE to 0.98 kg, the methanol to 1.65 kg, the TFE was injected to 0.60 MPa, the 50% methanol solution of di-n-propyl peroxide was changed to 0.060 kg, the PPVE was changed to 0.052 kg added for every 1 kg of TFE supplied, and the polymerization time was changed to 23 hours. Otherwise, the granules were obtained in the same manner as in Experimental Example 1.
[0160] Experimental Example 3
[0161] The pure water was changed to 49.0 L, the perfluorocyclobutane to 40.7 kg, the PPVE to 1.95 kg, the methanol to 3.80 kg, the TFE was injected to 0.64 MPa, the 50% methanol solution of di-n-propyl peroxide was changed to 0.041 kg, the PPVE was changed to 0.058 kg added for every 1 kg of TFE supplied, and the polymerization time was changed to 19 hours. Otherwise, the granules were obtained in the same manner as in Experimental Example 1.
[0162] Experiment Example 4
[0163] 51.8 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 40.9 kg of perfluorocyclobutane, 2.30 kg of perfluoropropyl vinyl ether (PPVE), and 2.38 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.64 MPa, followed by the addition of 0.103 kg of a 50% methanol solution of di-n-propyl peroxide dicarbonate, to initiate polymerization. Since the pressure within the system decreased as polymerization progressed, TFE was continuously supplied to maintain a constant pressure, with an additional 0.050 kg of PPVE added for every 1 kg of TFE supplied. Polymerization was terminated after the additional TFE supply reached 40.9 kg. Unreacted TFE was released, and the autoclave pressure was restored to atmospheric pressure. The resulting reaction product was then washed with water and dried to obtain 43.0 kg of powder.
[0164] The obtained powder was melt-extruded at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.) to obtain TFE / PPVE copolymer granules. Various physical properties of the obtained granules were determined using the method described above.
[0165] Experimental Example 5
[0166] 51.8 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 40.9 kg of perfluorocyclobutane, 2.37 kg of perfluoropropyl vinyl ether (PPVE), and 1.47 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.64 MPa, followed by the addition of 0.103 kg of a 50% methanol solution of di-n-propyl peroxide dicarbonate, to initiate polymerization. Since the pressure within the system decreased as polymerization progressed, TFE was continuously supplied to maintain a constant pressure, with an additional 0.052 kg of PPVE added for every 1 kg of TFE supplied. Polymerization was terminated after the additional TFE supply reached 40.9 kg. Unreacted TFE was released, and the autoclave pressure was restored to atmospheric pressure. The resulting reaction product was then washed with water and dried to obtain 43.0 kg of powder.
[0167] The obtained powder was melt-extruded at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.) to obtain TFE / PPVE copolymer granules. The PPVE content of the obtained granules was determined using the method described above.
[0168] The obtained granules were placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the reactor was temporarily evacuated, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another evacuation and introduction of F2 gas. This process of introducing F2 gas and evacuating the reactor was repeated once every hour, and the reaction was carried out at 210°C for 10 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction. Various physical properties of the fluorinated granules were measured using the above method.
[0169] Comparative Experiment Example 1
[0170] The amount of PPVE was changed to 2.43 kg, the amount of methanol was changed to 3.00 kg, and the amount of PPVE was changed to 0.053 kg added for every 1 kg of TFE supplied, resulting in 43.1 kg of dry powder. Otherwise, the granules were obtained in the same manner as in Experiment 4.
[0171] Comparative Experiment Example 2
[0172] The amount of pure water was changed to 26.6 L, the amount of perfluorocyclobutane was changed to 30.4 kg, the amount of PPVE was changed to 0.93 kg, the amount of methanol was changed to 4.20 kg, the pressure of TFE was increased to 0.58 MPa, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.021 kg, the amount of PPVE was changed to 0.035 kg added for every 1 kg of TFE supplied, the polymerization time was changed to 8 hours, and 15 kg of dry powder was obtained. Otherwise, granules were obtained in the same manner as in Experimental Example 1.
[0173] Comparative Experiment Example 3
[0174] The amount of PPVE was changed to 3.39 kg, the amount of methanol was changed to 3.51 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.070 kg added for every 1 kg of TFE supplied, resulting in 43.7 kg of dry powder. Otherwise, the same granules were obtained as in Experimental Example 4.
[0175] Comparative Experiment Example 4
[0176] The amount of PPVE was changed to 2.75 kg, the amount of methanol was changed to 3.79 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.058 kg added for every 1 kg of TFE supplied, resulting in 43.3 kg of dry powder. Otherwise, the same granules were obtained as in Experimental Example 4.
[0177] Using the granules obtained from the experimental and comparative experimental examples, various physical properties were determined using the methods described above. The results are shown in Table 3.
[0178] Table 3
[0179] Table 3
[0180]
[0181] The “<6” in Table 3 refers to the number of functional groups being less than 6.
[0182] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.
[0183] (Water vapor transmission rate)
[0184] Using granulation and a thermoforming machine, sheet-like test pieces with a thickness of approximately 0.2 mm were produced. These were then placed in a test cup (with a transparency area of 12.56 cm²). 2 Add 18g of water to the sample, cover it with a sheet test piece, and secure it tightly with a PTFE gasket. Allow the sheet test piece to remain in contact with the water. After maintaining this temperature at 95℃ for 30 days, remove it and let it stand at room temperature for 2 hours to measure the mass loss. Calculate the water vapor transmission rate (g·cm / m) using the following formula. 2 ).
[0185] Water vapor transmission rate (g·cm / m) 2 = Mass reduction (g) × Thickness of sheet test piece (cm) / Transmitting area (m²) 2 )
[0186] (Recovery Amount)
[0187] Approximately 2g of the aforementioned granules were added to a mold (13mm inner diameter, 38mm height). The mixture was then melted at 370°C for 30 minutes using a hot plate press, followed by water cooling while applying pressure at 0.2MPa (resin pressure) to produce a molded body with a height of approximately 8mm. The resulting molded body was then cut to produce a test piece with an outer diameter of 13mm and a height of 6mm. The test piece was then compressed at room temperature using a compression device to a compression set of 50% (i.e., compressing the 6mm high test piece to a height of 3mm).
[0188] The prepared test pieces were compressed at room temperature using a compression device to a compression set of 50% (i.e., compressing a 6mm high test piece to a 3mm high). With the compressed test pieces fixed in the compression device, they were placed in an electric furnace at 150°C for 18 hours. The compression device was removed from the furnace, and after cooling to room temperature, the test pieces were removed. The recovered test pieces were left at room temperature for 30 minutes, and their height was measured. The recovery amount was calculated using the following formula.
[0189] Recovery amount (mm) = t2 - t1
[0190] t1: Height of the spacer (mm)
[0191] t2: Height of the test piece removed from the compression device (mm)
[0192] In the above experiment, t1 = 3 mm.
[0193] (Storage modulus (E') at 150℃)
[0194] The dynamic viscoelasticity was determined using a DVA-220 (manufactured by IT Keisoku Seigyo). A thermoformed sheet with a length of 25 mm, a width of 5 mm, and a thickness of 0.2 mm was used as the sample. The measurement was conducted at a heating rate of 2 °C / min and a frequency of 10 Hz, within a temperature range of 30 °C to 250 °C, and the storage modulus (MPa) was recorded at 150 °C.
[0195] (Surface pressure at 150℃)
[0196] The surface pressure at 150°C is calculated from the results of the compression set test at 150°C and the storage modulus measurement at 150°C, according to the following formula.
[0197] Surface pressure at 150℃ (MPa) = (t2 - t1) / t1 × E'
[0198] t1: Height of the spacer (mm)
[0199] t2: Height of the test piece removed from the compression device (mm)
[0200] E': Energy storage modulus at 150℃ (MPa)
[0201] (Carbon dioxide permeability coefficient)
[0202] A sheet-like test piece with a thickness of approximately 0.1 mm was prepared using granulation and a hot press molding machine. Using the obtained test piece, the carbon dioxide transmittance was measured using a differential pressure gas transmittance meter (L100-5000 type gas transmittance meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. The transmittance area was found to be 50.24 cm². 2 The carbon dioxide transmittance was measured at a test temperature of 70℃ and a test humidity of 0%RH. Using the obtained carbon dioxide transmittance and the thickness of the test piece, the carbon dioxide transmittance coefficient was calculated using the following formula.
[0203] Carbon dioxide permeability (cm) 3 ·mm / (m 2·24h·atm))=GTR×d
[0204] GTR: Carbon dioxide transmittance (cm) 3 / (m 2 ·24h·atm))
[0205] d: Thickness of the test piece (mm)
[0206] (Long-term sealing performance evaluation)
[0207] The sealing performance was determined according to the methods described in ASTM D395 or JIS K6262:2013. A 13mm outer diameter and 8mm height molded body was prepared using granulation and a hot press. The resulting molded body was then cut to produce a 13mm outer diameter and 6mm height test piece. The test piece was compressed to 50% compression set at room temperature using a compression device. With the compressed test piece fixed in the compression device, it was placed in an electric furnace and heated at 65°C for 72 hours. The compression device was removed from the furnace, and after cooling to room temperature, the test piece was removed. The recovered test piece was left at room temperature for 30 minutes, and its height was measured. The recovered test piece was then compressed again to 50% compression set at room temperature using the compression device. With the compressed test piece fixed in the compression device, it was placed in an electric furnace and heated at 65°C for 428 hours (cumulative heating time 500 hours). The compression device was removed from the furnace, and after cooling to room temperature, the test piece was removed. After the recovered test pieces were left at room temperature for 30 minutes, their height was measured. The compression set was then calculated using the following formula.
[0208] Compression set (%) = (t0 - t2) / (t0 - t1) × 100
[0209] t0: Original height of the test piece (mm)
[0210] t1: Height of the spacer (mm)
[0211] t2: Height of the test piece removed from the compression device (mm)
[0212] In the above experiment, t0 = 6 mm and t1 = 3 mm.
[0213] In addition, the rate of change of sealing performance is calculated using the following formula.
[0214] Sealing performance change rate (%) = (CS) 500 -CS 72 ) / CS 72 ×100
[0215] CS 72 Compression set percentage after 72 hours of heating (%)
[0216] CS 500 Compression set (%) after 500 hours of heating
[0217] (Injection molding)
[0218] The copolymer was injection molded using an injection molding machine (Sumitomo Heavy Industries, Ltd., SE50EV-A) with a barrel temperature of 390°C, a mold temperature of 170°C, and an injection speed of 50 mm / s. A Cr-plated mold (100 mm × 100 mm × 2.5 mm, side gate) was used for HPM38. The surface of the resulting injection-molded body was visually inspected, and its smoothness was evaluated according to the following criteria.
[0219] 2: No roughness was observed on the surface; it was smooth.
[0220] 1: Roughness is observed only on the surface of the portion located near the gate of the mold.
[0221] 0: Roughness is observed on most of the surface.
[0222] (Water vapor leakage test)
[0223] Using an injection molding machine (Sumitomo Heavy Industries, SE50EV-A), with the barrel temperature set at 350℃~385℃ and the mold temperature set at 150℃~200℃, the copolymer was injection molded to obtain a gasket with an outer diameter of Φ17.7mm, an inner diameter of Φ14.3mm, and a thickness of 1.6mm.
[0224] like Figure 5 As shown, 2g of water 52 is added to an aluminum alloy cup 51. A gasket 6 is inserted between the cup 51 and the gasket compression clamp 53, and the cover 54 is tightened with bolts 55 to compress the gasket 6. A spacer 56 is placed between the cover 54 and the cup 51, and the compression deformation rate of the gasket 6 is adjusted to 50%. The mass of the test clamp 50 thus obtained is measured. The test clamp 50 is placed in a constant temperature bath heated to 95°C and left for 1000 hours. After being removed and left at room temperature for 2 hours, its mass is measured. The amount of water vapor leakage is calculated using the following formula. This operation is repeated 5 times, and the average amount of water vapor leakage is calculated. The average value is recorded in Table 4.
[0225] Water vapor leakage (g / 1000 hours) = (mass of the test fixture before heating) - (mass of the test fixture after heating)
[0226]
[0227] Symbol Explanation
[0228] 10 storage cells
[0229] 1 outer can
[0230] 2 lids
[0231] 3 bottom
[0232] 4A 1st external terminal
[0233] 4B 2nd external terminal
[0234] 5 bolts
[0235] 6 sealing components
[0236] 61 Cylindrical section
[0237] 62 Flange section
[0238] 63 Side wall portion
[0239] 7 Insulating components
[0240] 50 test fixtures
Claims
1. A sealing component comprising a copolymer containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, the perfluoro(propyl vinyl ether) units comprising 4.0% to 6.0% by mass relative to all monomer units, the copolymer comprising a melt flow rate of 26 g / 10 min to 37 g / 10 min, and per 10 6 The main chain carbon atoms have more than 50 functional groups, wherein the functional groups are -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH, and the sealing component has a thickness of 0.5mm to 2.5mm and a sealing area of 0.5cm². 2 ~50cm 2 Furthermore, the sealing component is in a state of compression deformation rate of 20% to 60%.
2. The sealing component as claimed in claim 1, wherein, The copolymer has a melting point of 301℃~317℃.
3. The sealing component as claimed in claim 1 or 2, wherein, The heat of fusion of the copolymer is above 24.0 mJ / mg.
4. The sealing member according to any one of claims 1 to 3, wherein, The copolymer has a fluorine content of less than 70 mol%.
5. The sealing component as described in any one of claims 1 to 4, wherein it is an injection-molded body or a transfer-molded body.
6. An energy storage device comprising a sealing component according to any one of claims 1 to 5.
7. The energy storage body as claimed in claim 6, comprising: Outer packaging cans Electrical components housed within the outer can, The cap that blocks the opening of the outer can, and The terminal is located on the outside of the cover. The sealing component is held between the cover and the external terminal.
Citation Information
Patent Citations
Flat nonaqueous electrolyte secondary battery
JP2010056079A
Sealing material
CN103946250A
Tetrafluoroethylene polymerization process
EP0271243A1